Relevansi Pemikiran Pendidikan Abdurrahman Wahid dan Abdurrahman An-Nahlawi di Era Modern - Kasanah, Siti (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2021)
This article aimed to find out the appropriateness of educational thinking according to Abdurrahman Wahid and Abdurrahman An-Nahlawi which includes an understanding of education and its objectives, principles of education, educators, students, methods, curriculum, environment and also its correlation to the modern world. This research study is focused on the compatibility of Abdurrahman Wahid and Abdurrahman An-Nahlawi's education with the modern world. The results of this study show that the concept of education based on the thoughts of Abdurrahman Wahid and An-Nahlawi is still very relevant to education in this modern era. Basically the purpose of their education is not only to transfer knowledge but to transfer moral values and goodness. the contents and also the methods offered are still suitable and can be applied because Islamic education theories that are used are adapted to the psychological approach, which uses the ability of reason.